Understanding Severe Exploitation Requires a Human Rights and Gender-Sensitive Intersectional Approach - Giammarinaro, Maria Grazia (Frontiers in Human Dynamics, 2022)
This paper discusses the notion of severe exploitation in relation to production and social reproduction, and argues that the existence of huge “edge populations” subject to severe exploitation, mainly involving migrants, is a structural component of global economies, and thus requires primarily not a criminal law but rather a human rights and social justice response. “Edge populations” are targeted for severe exploitation because of intersectional vulnerabilities. A gender perspective implies an analysis of how intersectional factors impact differently women's, men's and LGBTIQ+ lives; this study is however mostly based on women's experiences of severe exploitation and related vulnerabilities. Three sectors prone to severe exploitation have been analyzed, in which weak regulations, and deprivation of rights expose migrants, especially migrants in irregular situations including migrant women, to various forms of severe exploitation. Through an analysis of domestic work, agriculture and the sex industry, this paper highlights that, although in different degrees, a combination of vulnerability and agency, of coercion and negotiation, exists in most cases of severe exploitation. The study suggests that a notion of “gender intersectional exploitation” should be further explored.